Progress and prospects of research on wetland concession system - LIU Qianqian, XU Ruiliang, JIN Cheng, SUN Dongfang (Ziyuan Kexue)
[Objective] Concession system is a new path to realize scientific protection and rational development of wetland resource assets, and it is also a key practice of ecological civilization construction in the new era. Analyzing the research framework, characteristics, and development trends of wetland concession systems both domestically and internationally can provide scientific reference for the pilot work of wetland concession system in China. It also holds significant theoretical and practical implications for the study of natural resource asset delegation and agency mechanisms. [Methods] This paper combines systematic review with bibliometric methods, utilizing CiteSpace software for co-occurrence visualization analysis, to summarize the characteristics of wetland concession system research, identify existing issues, and propose prospects for future research on wetland concession systems. [Results] The results show that: (1) Studies in China follow the line of object-relationship-mechanism, while international studies focus on concession-environmental-individual; (2) Studies in China have undergone three stages of change, with increasing policy guidance orientation. The change of international studies is less distinct, with a stronger focus on problem analysis; (3) In terms of institutional arrangement and policy recommendations, both Chinese and international studies are based on the inductive method, but there are methodological differences in problem-oriented perspective; (4) The wetland concession system with Chinese characteristics includes a multi-level rights and responsibility system, multi-stakeholder collaborative participation system, multi-path value realization system, and multi-type managemental guarantee system, featuring systematicity and high efficiency. [Conclusion] In the context of exploring the pilot wetland concession system and the current situation that practice is leading theoretical research, this article proposed to conduct a problem-oriented research by combining the theories of property rights, sustainable development, and community promotion. Meanwhile, the pilot practice should pay more attention to the holisticness of policy, systematicity of supervision, scientific quality of competition, and participation of residents.